Gold levels produced by treatment with auranofin and sodium aurothiomalate. - Lewis, D (1983)
Sixty-three patients with rheumatoid arthritis were randomly divided into 3 groups, and treated with either sodium aurothiomalate (Myocrisin), auranofin, or placebo. Gold levels in whole blood, plasma, and haemolysate were measured serially along with clinical and laboratory parameters of efficacy. Auranofin produced a higher ratio of haemolysate to plasma gold than Myocrisin, and it appears that the affinity of the red cell for gold is reduced during therapy with auranofin. Gold levels did not correlate with changes in the pain score, erythrocyte sedimentation rate, and C-reactive protein, nor with the development of toxicity. In the Myocrisin group the haemolysate gold level achieved was dependent on the number of cigarettes smoked. In the auranofin group there was no such correlation, but the haemolysate gold level was higher for smokers than non-smokers. The likely action of gold is discussed.